Intellectual Properties and Sustainable Development Goals; Analysis of 2030 Agenda in Promoting Intellectual Property Rights - Dulume, Wakgari (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2019)
Intellectual Property has existed for decades, even centuries in some instance; with the purpose of promoting social welfare through novelty and research activities. Intellectual property rights have been and more importantly became economically and politically important than they were nowadays. Intellectual Property is becoming crucial economic development in modern world; particularly in developed countries. The 2030 Agenda for sustainable development also included importance of Intellectual Property. The paper analyzed the place of Intellectual Property in the 2030 Agenda with particular reference to goal 17 of Sustainable Development Goals. The paper employed qualitative method; mainly review of relevant literature on Intellectual Properties and Sustainable Development Goals. The 2030 Agenda document, mainly goal 17 is discussed in detail. The article argues protecting intellectual property promote innovation and technological development. The finding claims 2030 Agenda recognized intellectual property protection encouraging North-South and South-South partnership for its promotion; particularly to enable developing and least developed countries. The agenda seems to recognize one size fits all approach does not work in intellectual property protection; as different development stage require different intellectual property protection system. Thus, developing states can enjoy flexibility of loose intellectual property protection system to promote technological transfer and innovation. More importantly, developing policies that integrate intellectual property, capacitating individuals and groups on invention is required before going for strong intellectual property protection.